Antioxidant Activity of Acacia nilotica Bark † - V. Krishnaraju, Alluri; Sushruta, Koppula; V. Subbaraju, Gottumukkala (Asian Journal of Chemistry, 2010)
Aqueous extract of the bark of A. nilotica showed strong antioxidant activity in nitroblue tetrazolium (NBT) photoreduction method. Bioactivity guided isolation of the extractives of the bark led to the identification of gallic acid as the source f antioxidant activity.